The art of placemaking interpreting community through public art and urban design - Fleming, Ronald Lee (Merrell Publishers, 2007)
"In The Art of Placemaking, Ronald Lee Fleming adopts a practical approach to tackling public art and community planning in the US as they are experienced today. Through detailed, in-depth case studies he discusses the development of placemaking initiatives since 1990, accompanying beautiful and approachable examples with constructive criticism of those he sees as less successful. The case studies deal with varied projects, ranging from a clock with bronze bells that marks the gateway to downtown Cincinnati to the beautification of a water treatment plant in Cambridge, Massachusetts; and from a terrazo floor incorporating sea-creatures at Miami International Airport, Florida, to a firefighters' memorial in Boston. An informative introduction puts the projects in context, and the book also contains essays on what we can learn from the past, how failed projects can be redeemed, and the evolution of state funding. Illuminating interviews with artists and an extensive bibliography are also included." -- Provided by publisher.